Feasibility and costs of water fluoridation in remote Australian Aboriginal communities - Ehsani Jonathon P; Bailie Ross (BMC, 2007)
Abstract Background Fluoridation of public water supplies remains the key potential strategy for prevention of dental caries. The water supplies of many remote Indigenous communities do not contain adequate levels of natural fluoride. The small and dispersed nature of communities presents challenges for the provision of fluoridation infrastructure and until recently smaller settlements were considered unfavourable for cost-effective water fluoridation. Technological advances in water treatment and fluoridation are resulting in new and more cost-effective water fluoridation options and recent cost analyses support water fluoridation for communities of less than 1,000 people. Methods Small scale fluoridation plants were installed in two remote Northern Territory communities in early 2004. Fluoride levels in community water supplies were expected to be monitored by local staff and by a remote electronic system. Site visits were undertaken by project investigators at commissioning and approximately two years later. Interviews were conducted with key informants and documentation pertaining to costs of the plants and operational reports were reviewed. Results The fluoridation plants were operational for about 80% of the trial period. A number of technical features that interfered with plant operation were identified and addressed though redesign. Management systems and the attitudes and capacity of operational staff also impacted on the effective functioning of the plants. Capital costs for the wider implementation of these plants in remote communities is estimated at about $US94,000 with recurrent annual costs of $US11,800 per unit. Conclusion Operational issues during the trial indicate the need for effective management systems, including policy and funding responsibility. Reliable manufacturers and suppliers of equipment should be identified and contractual agreements should provide for ongoing technical assistance. Water fluoridation units should be considered as a potential priority component of health related infrastructure in at least the larger remote Indigenous communities which have inadequate levels of natural fluoride and high levels of dental caries.